A perennial problem? On underoccupation in English council housing. Issue 2 (7th February 2019) - Cowan, Dave; Marsh, Alex
Abstract: Addressing the issue of underoccupation has been a prominent feature in English social housing policy since the Conservative-Liberal Democrat Coalition government was formed in 2010. A key move under the Coalition's welfare reform agenda was the implementation of the underoccupancy penalty—the so-called 'bedroom tax'—from April 2013. However, while this policy triggered high-profile protests, it does not represent a novel policy preoccupation. Variations on the theme have recurred in housing policy debates almost since the advent of council housing. This paper adopts a long-term perspective and presents a sociological institutionalist analysis which focuses on the mechanisms through which underoccupation has been governed. Drawing on a range of archival material, we argue that the government of underoccupation has undergone revealing transformations over the period since 1929. Not only does the broader policy context—understandings of the purpose of social housing and the role it fulfils in the housing market—differ over time, but, at the more detailed level of policy instruments, the mechanisms proposed to address underoccupation differ in ways that can be explained in terms of prevailing policy logics and institutional structures. Most significantly, the nature of the underoccupation problem has been framed differently: the rationales offered as justification for policy action draw on very different vocabularies, in ways that allow us to trace the influence of more fundamental shifts in policy discourse into the domain of housing policy.